Identification of lipid metabolism-related biomarkers and prognostic analysis in geriatric patients with sepsis - Bian, Yeping; Xu, Jian; Deng, Xiaojing; Zhou, Suming; Tong, Jiayi (The Journal of Infection in Developing Countries, 2024)
Introduction: This study aimed to find the lipid metabolism-associated biomarkers in geriatric patients with sepsis. Methodology: The gene expression profiles of specimens from geriatric patients with sepsis were retrieved from the Gene Expression Omnibus database. Differentially expressed genes were obtained via “limma” R package, and modules and genes highly associated with geriatric patients with sepsis were screened via “WGCNA” R package. The study also involved conducting enrichment analyses using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes, as well as analyzing protein-protein interaction networks. The receiver operating characteristic curves were employed to determine the diagnostic values of hub genes. Results: A total of 73 differentially expressed lipid metabolism-related genes (DELRGs) were retained from the 1,317 differentially expressed genes, 8,335 module genes, and 1,045 lipid metabolism-related genes. The Gene Ontology and Kyoto Encyclopedia of Genes and Genomes results showed that DELRGs were mostly related to lipid metabolism. We identified ten hub genes from the protein-protein interaction network of DELRGs. The result of receiver operating characteristic validation indicated that seven hub genes (PPARG, ACSL1, IRS2, PLA2G4A, ALOX5, SPTLC1, and JAK2) worked as the biomarkers of geriatric patients with sepsis. The prognostic nomogram suggested that the set of seven hub genes can be utilized to evaluate the mortality risk. Conclusions: We screened seven lipid metabolism-related hub genes with diagnostic values. These molecules may exert a pivotal influence on the progression of sepsis in geriatric patients, as potential biomarkers and therapeutic targets.